Essentials of econometrics - Gujarati, Damodar (Singapore : McGraw-Hill, 1992)
Basics of probability and statistics. The linear regression model. Regression analysis in practice.
Keywords: Economics; Econometrics; Econometrics; Economics -- Statistical methods